The Effectiveness of Using Extensive Reading Approach Combined with Literature Circle Strategy Toward Students' Reading Ability - Riswanto Riswanto; Reko Serasi; Esni Senvita; Kasmaini (Journal of English Education and Teaching, 2023)
This study aims to determine whether there is effect of using Extensive Reading Approach Combined with Literature Circle Strategy on Students’ Reading Ability. The research used Quantitative Approach with Quasi Exsperimental Design. The population of this research was the students of English Education Study Program at UINFAS Bengkulu academic years 2022/2023, 40 students were taken as sample. The sampling technique used in this research was purposive sampling. In this study, 6A was used as an experimental class and 6C was used as an control class The data were collected by using reading comprehension test. The data obtained were analyzed by using t-test formula. Based on the table p-output of Sig. (2-tailed) was 0,000< 0,05 and t-count value was 4,260, while the t table's df= n-2 = 40-2 was 38. (2,024). Based on the t-distribution table's ta=t.0,025 value. It can be said that H0 was rejected and Ha was accepted. It showed that there was effect of using Extensive Reading Approach combined with Literature Circle Strategy on students’ reading ability.